THE EFFECT OF DIFFERENT LEVELS OF VITAMIN E ON THE REPRODUCTIVE PERFORMANCE OF ZEBRAFISH (Danio rerio) - Utomo, N.B.P; Junior, M. Zairin; Yusuf, T.L.; Mokoginta, I.; Bintang, M. (Indonesian Society of Scientific Aquaculture (ISSA), 2005)
This experiment was conducted to determine the dietary Vitamin E requirement for reproduction of broodstock zebrafish Danio rerio. Four isonitrogenous (39% crude protein) and isocaloric (3,260 kcal digestible energy/kg diet) practical diets, namely diets A, B, C, and D with different levels of Vitamin E were fed to zebrafish broodstock. The broodstock were cultivated in aquaria. Diet A contained low dosage of Vitamin E (5 mg Vitamin E /kg diet), while diets B (62 mg Vitamin E /kg diet), C (125 mg Vitamin E /kg diet), and diet D (187 mg Vitamin E /kg diet), combined respectively with 1% n-3 fatty acids and 2% n-6 fatty acids. Fish were fed ad satiation for 60 days using these diets. During feeding period, gonad maturation stages were examined. The dietary with different level of Vitamin E affected egg size, chemical content, total number of larvae, normal larvae, and survival rate of larvae produced, fecundity, fertilization rate, and hatching rate. On the other hand, fish fed on experimental diets did not show any significance differences in the gonad somatic index, fecundity, fertilization rate, and hatching rate. Fish fed on diet D produced the highest fecundity (633.65 ± 71.86 eggs/grams of fish), fertilization rate (92.3 ± 7.7%), and hatching rate (80.31 ± 9.8%). The total lipid content of eggs were significant, ranging from D (39.7%), C (33.5%), B (32.1%), and A (29.5%). At a dosage of 1% of dietary n-3 fatty acids and 2% n-6 fatty acids, zebrafish require 187 mg Vitamin E/kg feed in the diet for reproduction. . Keywords: vitamin E, reproductive performance, Danio rerio ABSTRAK Penelitian ini ditujukan untuk mengetahui kebutuhan Vitamin E pada pakan induk ikan zebra (Danio rerio) untuk reproduksi. Empat pakan perlakuan yang iso-protein (39%) dan iso-kalori (3.260 kcal digestible energy/kg pakan), dinamakan pakan A, B, C, dan pakan D dengan kandungan Vitamin E yang berbeda diberikan kepada induk ikan zebra. Induk ikan dipelihara pada akuarium. Pakan A mengandung Vitamin E terendah (5 mg Vitamin E/kg pakan), sedangkan pakan B mengandung Vitamin E 62 mg Vitamin E/kg pakan, pakan C asam mengandung Vitamin E 125 mg /kg pakan, dan pakan D mengandung Vitamin E 187 mg /kg pakan. Semua pakan perlakuan mempunyai kombinasi asam lemak n-3 berbanding n-6 sebesar 1:2. Ikan diberi pakan secara ad satiation selama 60 hari pemeliharaan. Selama masa pemberian pakan, tingkat kematangan gonad diperiksa secara teratur. Perbedaan kandungan vitamin E dalam pakan mempengaruhi fekunditas, derajat pembuahan telur, serta derajat penetasan telur. Pakan perlakuan tidak mempengaruhi nilai gonad somatik indeks dan kelangsungan hidup larva umur 3 hari. Pemberian pakan D menghasilkan fekunditas (633.65 ± 71.86 telur/gram induk), derajat pembuahan telur (92.3 ± 7.7%), serta derajat penetasan telur (80.31 ± 9,8%) terbaik. Total kandungan lemak pada telur berbeda nyata, yaitu pada pakan D (39.7%), C(33.5%), B(32.1%), dan pakan A(29.5%). Pada kandungan 1% asam lemak n-3 dan 2% asam lemak n-6, ikan zebra membutuhkan 187 mg Vitamin E/kg pakan untuk reproduksi yang normal. Kata kunci: Vitamin E, penampilan reproduksi, Danio rerio